Hands in the Till : Embezzlement of Public Monies in Mississippi - Crockett, James R. (Book collections on Project MUSE., 2007)
In 2004 Corporate Crime Reporter asserted that Mississippi was the most crooked state in America. By comparing the number of federal corruption convictions over the past decade and the 2002 population of the state, the conclusion was inescapable. Too many officials were robbing the public they had sworn to serve and protect. Hands in the Till: Embezzlement of Public Monies in Mississippi establishes the scope of a major crisis in a poor state where needs are many and funds are scarce. The book highlights the tireless work of the Office of the State Auditor in investigating the theft of public.